"What alternative punishment is there?": Military Executions During World War I - Oram, Gerard Christopher (2000)
The power to inflict the death penalty formed a vital part of the disciplinary process in all the major armies during the First World War. Yet serious historians have neglected the subject. This thesis addresses the topic in a critical manner and challenges the view that executions were arbitrary, reflecting a distant and uncaring High Command. Analysis of military and criminal law in Europe and the United States establishes a comparative framework from which to proceed. Changing ideas about discipline and duty as the war impacted on both the military and British society are assessed. The concept of morale - so important to military commanders during the war - is evaluated in the context of changing demands on the army as it adjusted to the absorption of 'citizen soldiers' and conscripts as well as disappointment on the battlefield. Differences between Regular, Territorial and 'New Army' formations are assessed. So too is the impact of the big offensives such as the Battle of the Somme in 1916. Finally, three divisions (one Regular, one Territorial, and one 'New Army') are subjected to detailed analysis from their initial deployment on the Western Front then on to the Italian Front where a different disciplinary approach can be detected. The central theme of the thesis is that whilst some British commanders adopted a progressive approach to discipline most clung to traditional ideas of deterrence. In this they were encouraged by the very nature of British military law which differed from continental and American models in vital areas. Driven by the fear of a collapse in discipline amongst their 'citizen soldiers' some commanders took refuge in traditional methods of punishment to maintain what they termed 'fighting spirit'. This, however, altered at the end of 1917 when traditional approaches gave way to new forms of management